2005
DOI: 10.5194/acp-5-2055-2005
|View full text |Cite
|
Sign up to set email alerts
|

Trends of halon gases in polar firn air: implications for their emission distributions

Abstract: Abstract. Four halons

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 26 publications
(49 reference statements)
4
28
0
Order By: Relevance
“…This distribution shift is based on the assumption that CFC-113a emissions are predominantly from Europe and North America at the beginning of the model run and then shift to be coming predominantly from East Asia towards the end of the model run. The latter is consistent with our measurements from Taiwan (Section 3.2.1) and previous work has found that 145 emissions of ozone depleting substances shifted from more northerly Northern Hemisphere latitudes to more southerly Northern Hemisphere latitudes (Reeves et al, 2005;Montzka et al, 2009). This is likely due to developing countries, which are mostly located further south, having more time to phase out the use of many ODSs than developed countries (Newland et al, 2013;CTOC, 2014;Fang et al, 2016).…”
Section: Emission Modellingsupporting
confidence: 82%
See 1 more Smart Citation
“…This distribution shift is based on the assumption that CFC-113a emissions are predominantly from Europe and North America at the beginning of the model run and then shift to be coming predominantly from East Asia towards the end of the model run. The latter is consistent with our measurements from Taiwan (Section 3.2.1) and previous work has found that 145 emissions of ozone depleting substances shifted from more northerly Northern Hemisphere latitudes to more southerly Northern Hemisphere latitudes (Reeves et al, 2005;Montzka et al, 2009). This is likely due to developing countries, which are mostly located further south, having more time to phase out the use of many ODSs than developed countries (Newland et al, 2013;CTOC, 2014;Fang et al, 2016).…”
Section: Emission Modellingsupporting
confidence: 82%
“…The emissions distribution used for CFC-113 was assumed to be constant for the whole of the model run. This distribution has been used in previous studies for similar compounds (McCulloch et al, 1994;Reeves et al, 2005;Laube et al, 2014Laube et al, , 2016 and has been shown to reproduce the reported mixing ratios of CFC-135 11 and CFC-12 at Cape Grim to within 5 % uncertainty (Reeves et al, 2005). We decided to select an emission distribution for CFC-113a based on how well the modelled mixing ratios in the latitude band 48.6-56.4° N agreed with the observations at Tacolneston.…”
Section: Emission Modellingmentioning
confidence: 99%
“…The model grid is divided into 24 equal area, zonally-averaged bands and has 12 vertical layers of 2 km depth. The model has been described elsewhere (Hough, 1989(Hough, , 1991 and has recently been used to study the temporal behaviour and global distribution of halons (Fraser et al, 1999;Reeves et al, 2005) and HFC227ea (Laube et al, 2010a). The latitudinal distribution of emissions is based on a function of industrial activity such that 95 % of emissions are in the Northern Hemisphere, primarily from mid-latitudes (Reeves et al, 2005).…”
Section: Global Emission Estimatesmentioning
confidence: 99%
“…The latitudinal distribution of emissions is based on a function of industrial activity such that 95 % of emissions are in the Northern Hemisphere, primarily from mid-latitudes (Reeves et al, 2005). Under these conditions the model's transport scheme has been shown to reproduce the observed global distributions of CFC-11 and CFC-12 (Reeves et al, 2005). For c-C 4 F 8 , using an atmospheric lifetime of 3200 yr (Forster et al, 2007), the emissions into the model were varied until the predicted concentrations matched the Cape Grim observations.…”
Section: Global Emission Estimatesmentioning
confidence: 99%
“…The isotopic composition of N 2 O ( 15 N and 18 O) also proves interesting for a better understanding of processes at the origin of atmospheric variations and of the artifacts recorded in ice cores (Sowers, 2001). Many other gaseous species such as CO (Haan et al, 1996;Haan and Raynaud, 1998;Haan et al, 1996;Haan and Raynaud, 1998), COS (Sturges et al, 2001a), various chlorine, bromine and iodide, and other species of interest for atmospheric chemistry (Sturges et al, 2001b;Reeves et al, 2005) have also been measured in firn and ice. The Vostok data published in the eighties and nineties led to the idea that the variations in greenhouse gases have played an important climatic role in the past as amplifiers vis-à-vis changes in insolation (Genthon et al, 1987;Lorius et al, 1990;Jouzel et al, 1993;Petit et al, 1999).…”
Section: Greenhouse Gases and Other Properties Recorded In The Entrapmentioning
confidence: 99%